Penerapan Game Based Learning dalam Bimbingan Klasikal untuk Meningkatkan Komunikasi Interpersonal - Desanda Puspitasari (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2026)
This study aims to improve the interpersonal communication skills of Class X-4 students at SMA Negeri 7 Semarang through classical guidance services using the game-based learning method. Based on the Student Needs Assessment (AKPD), 27 out of 35 students experienced low self-confidence, rarely interacted with others, and had difficulties communicating with the opposite sex or adults. This study employed the Guidance and Counseling Action Research (PTBK) method in two cycles. The results of the paired sample t-test showed that the increase from the pre-test to post-test 1 was not significant (from 94.94 to 97.66; sig. = 0.051), but became significant in post-test 2 (102.23; sig. = 0.000). The average test score also increased from 98 (79%) in cycle I to 102 (82%) in cycle II. These findings indicate that the game-based learning method is effective when applied in classical guidance to improve students’ interpersonal communication skills.